The Mechanisms Behind Rapid Antidepressant Effects of Ketamine: A Systematic Review With a Focus on Molecular Neuroplasticity - Kang, Melody J. Y.; Hawken, Emily; Vazquez, Gustavo Hector (Frontiers in Psychiatry, 2022)
The mechanism of action underlying ketamine’s rapid antidepressant effects in patients with depression, both suffering from bipolar disorder (BD) and major depressive disorder (MDD) including treatment-resistant depression (TRD), remains unclear. Of the many speculated routes that ketamine may act through, restoring deficits in neuroplasticity may be the most parsimonious mechanism in both human patients and preclinical models of depression. Here, we conducted a literature search using PubMed for any reports of ketamine inducing neuroplasticity relevant to depression, to identify cellular and molecular events, relevant to neuroplasticity, immediately observed with rapid mood improvements in humans or antidepressant-like effects in animals. After screening reports using our inclusion/exclusion criteria, 139 publications with data from cell cultures, animal models, and patients with BD or MDD were included (Registered on PROSPERO, ID: CRD42019123346). We found accumulating evidence to support that ketamine induces an increase in molecules involved in modulating neuroplasticity and that these changes are paired with rapid antidepressant effects. Molecules or complexes of high interest included glutamate, AMPA receptors (AMPAR), mTOR, BDNF/TrkB, VGF, eEF2K, p70S6K, GSK-3, IGF2, Erk, and microRNAs. In summary, these studies suggest a robust relationship between improvements in mood, and ketamine-induced increases in molecular neuroplasticity, particularly regarding intracellular signalling molecules.